Reflections on two years after establishing an orthogeriatric unit: a focus group study of healthcare professionals' expectations and experiences - C. Abrahamsen; B. Nørgaard; E. Draborg; D. Nielsen (BMC, 2017)
Abstract Background For decades hospitals have been "vertically" organized, with the risk that specialization leads to fragmented and one-sided views of patient care and treatment that may cause poor communication and coordination of care and treatment. Two years after the introduction of an orthogeriatric unit for elderly patients admitted with fragility fractures, we studied the involved healthcare professionals' perspectives and experiences with working in an interprofessional organization. Methods We performed four focus groups interviews with 19 healthcare workers representing different professions. The interviews were analysed using systematic text condensation (STC). Results Three themes were identified: 1) A patient-centred approach, 2) An opportunity for professional growth and 3) The benefits of interprofessional collaboration. The interviewees emphasized in particular the systematic and frequent face-to-face communication enabled by the interprofessional team meetings as essential to their feeling of enhanced collegial solidarity. All groups expressed their respect for other groups' competences and their vital contributions to good orthogeriatric care. However, collaboration was challenged by the groups' divergent views of the patients and of the relevance of the information given in the weekly meetings. Heavy workloads were also mentioned. The opportunity for professional growth was also felt to be imperilled by some professionals. Conclusions All participants indicated their view that the orthogeriatric organization had improved the quality of care and treatment. Furthermore, good communication, mutual respect for other professional competences and shared goals were found to have enhanced interprofessional collaboration and improved the sense of having a shared mission. However, differences in approaches and expectations continued to challenge the orthogeriatric model after 2 years. Neither did all professionals find orthogeriatric care professionally challenging.